Heritability and Correlation Among Physiological and Yield Traits in Chickpea (Cicer arietinum L.) - Mian Safwat Ali Gul; Aizaz Akbar; Afraz Nasim; Muhammad Hasham Khan; Muhammad Ibrahim; Farooq Khan; Muzammil Ahmad; Mian Kehan Ali Gul; Maria Asad; Mian Asfahan Ali Gul (AGRIVITA Journal of Agricultural Science, 2023)
The present research assessed 18 Desi chickpea genotypes at the University of Agriculture Peshawar from November 2020 to May 2021. The plant material was grown using randomized complete block design with three replications to determine genetic variability, heritability, and correlation. Twelve parameters were studied encompassing two phenological and physiological; and eight morpho-yield traits. Significant differences (P<0.05) were estimated for all traits except excise leaf water retention. Genotypes IG2 exhibited early (99-days) flowering. EG1 showed the optimal height (52.45 cm). Furthermore, IG2 displayed maximum (17.11) productive branches per plant. FG1 recorded maximum (52) pod per plant. Meanwhile, IG2 also expressed maximum relative water content, seeds per pod (1.72), biological yield (3765.43 kg/ha), hundred-seed weight (32.43 g), and seed yield (1061.73 kg/ha). However, the maximum harvest index was recorded for genotype GG1. High heritability was registered for seeds per pod (0.74) and flowering days (0.75). Percent genetic advance was the highest for harvest index (62.08%), followed by seeds per pod (33.56%). Seed yield observed a significant positive correlation with seeds per pod (r=0.99**), hundred-seed weight (r=0.99**), biological yield (r=0.81**), plant height (r=0.54**), and productive branches per plant (r=0.49*). Therefore, these traits might indirectly select greater-yielding chickpea genotypes. Genotypes IG2, and BG2, are recommended for future breeding programs developing high-yielding chickpea cultivars.